The Scleractinia (Cnidaria: Anthozoa) of Abu-Musa and Sirri Islands, Persian Gulf - Salimi, Parisa Alidoost (Zool Stud, 2018)
Parisa Alidoost Salimi, Pargol Ghavam Mostafavi, Chaolun Allen Chen, Seyed Mohammad Reza Fatemi, and Michel Pichon (2018) There are many islands in the Iranian waters, but little is known about their coral species. This is a first attempt to describe and illustrate the coral species occurring in Abu-Musa and Sirri Islands. Overall, 26 species belonging to 9 families are reported, and three unidentified species and two species are added to coral communities of Iran. This study also provides overall insight on coral fauna in the Persian Gulf.